O simbolismo do "trabalho" na tradição sufi à luz da psicologia jungiana - Polonio, Andriete (2010)
This dissertation focuses the Sufi Tradition rooted in Brazil which follows the Haqshbandi line. . As hypothesis there is a possibility of a relation between the dynamics of the inner work of that school which appears in its symbols and the path of transformation and change of the psychical development according to the main lines of Jung´s psychology. The dissertation begins with the canary of Sufism and Sufi Tradition. Afterwards, the main symbols of that Tradition are exposed. The last step focuses the relation between the individuation process which is central in Jung´s psychology and the symbolic work which achieves the inner Sufi development